2008
DOI: 10.1254/jphs.08163fp
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Voltage-Gated Sodium Channel NaV1.8 in the Regulation of the Release and Synthesis of Substance P in Adult Mouse Dorsal Root Ganglion Neurons

Abstract: Abstract. This study was conducted to determine whether Na v 1.8 contributes to the release and/ or synthesis of substance P (SP) in adult mice dorsal root ganglion (DRG) neurons. The SP released from cultured DRG neurons of Na v 1.8 knock-out mice exposed to either capsaicin or KCl was significantly lower than that from wild-type (C57BL / 6) mice based on a radioimmunoassay. The SP level of L6 DRG in Na v 1.8 knock-out mice was also lower than that in wild-type mice. After chronic constriction injury (CCI) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…2). We selected DRG as an appropriate specimen because DRGs plays an important role in initiation, transmission, and maintenance of the neuropathic pain (19). Here we further found that DB, as well as diclofenac, exhibited strong inhibitory effects on the CCI-induced increases in COX-2 induction, PPT-A mRNA expression, and nociceptive sensitization.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…2). We selected DRG as an appropriate specimen because DRGs plays an important role in initiation, transmission, and maintenance of the neuropathic pain (19). Here we further found that DB, as well as diclofenac, exhibited strong inhibitory effects on the CCI-induced increases in COX-2 induction, PPT-A mRNA expression, and nociceptive sensitization.…”
Section: Discussionmentioning
confidence: 55%
“…; Wako, Osaka) according to previously described methods (19). Young adult male Wistar rats (6 -9 weeks of age) were divided into groups in the same way as in the carrageenan test and received intragastric administration of the test agents for 30 consecutive days.…”
Section: Peripheral Nerve Injurymentioning
confidence: 99%
“…Substance P is a specific indicator of C-fibber neurons, and plays an important role in pain signal transmission by potentiating nociceptive signaling and revealing pain-related behavior [ 16 , 20 ]. Our previous data indicated that the synthesis and release of substance P can be blocked by inhibition of COX-2 induction in the L5 DRG of CCI neuropathic rats.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, aberrant synthesis and release of substance P are evoked from DRG neurons. Following the reduction of substance P level in intracellular substance P pools evoked by the released substance P, a signal will be elicited to convey information for the transcripts of nuclear PPT-A genes to increase the substance P synthesis [ 20 ]. The released substance P may bind to its receptor (neurokinin-1 receptor), eliciting a signal to further release the substance P [ 3 ] and enhancing further up-regulation of β-catenin signaling [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The DRGs of 6-week-old male Wistar rats were dissociated into single cells (6 DRGs /dish or 3 DRGs/ well) according to a previously described method (8). The cells were cultured in 35-mm dishes or 24-well plates in Dulbecco's modified Eagle's medium (DMEM; Nissui Pharmaceutical, Tokyo) plus 10% heat-inactivated horse serum, 1% penicillin/streptomycin, and 200 mM glutamine and maintained at 37°C in a water-saturated atmosphere with 5% CO 2 for 5 days before the experiment.…”
Section: +mentioning
confidence: 99%